Tumor sink effect in 68Ga-PSMA-11 PET: myth or reality? - Gafita, Andrei; Wang, Hui; Robertson, Andrew; Armstrong, Wesley R.; Zaum, Raphael; Weber, Manuel; Yagubbayli, Farid; Kratochwil, Clemens; Grogan, Tristan R.; Nguyen, Kathleen; Navarro, Fernando; Esfandiari, Rouzbeh; et al. (Journal of nuclear medicine, 2022)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - We aimed to systematically determine the impact of tumor burden on 68Ga-prostate-specific membrane antigen-11 (68Ga-PSMA) PET biodistribution by the use of quantitative measurements. Methods: This international multicenter, retrospective analysis included 406 men with prostate cancer who underwent 68Ga-PSMA PET/CT. Of these, 356 had positive findings and were stratified by quintiles into a very low (quintile 1, ≤25 cm3), low (quintile 2, 25-189 cm3), moderate (quintile 3, 189-532 cm3), high (quintile 4, 532-1,355 cm3), or very high (quintile 5, ≥1,355 cm3) total PSMA-positive tumor volume (PSMA-VOL). PSMA-VOL was obtained by semiautomatic segmentation of total tumor lesions using qPSMA software. Fifty prostate cancer patients with no PSMA-positive lesions (negative scan) served as a control group. Normal organs, which included salivary glands, liver, spleen, and kidneys, were semiautomatically segmented using 68Ga-PSMA PET images, and SUVmean was obtained. Correlations between the SUVmean of normal organs and PSMA-VOL as continuous and categoric variables by quintiles were evaluated. Results: The median PSMA-VOL was 302 cm3 (interquartile range [IQR], 47-1,076 cm3). The median SUVmean of salivary glands, kidneys, liver, and spleen was 10.0 (IQR, 7.7-11.8), 26.0 (IQR, 20.0-33.4), 3.7 (IQR, 3.0-4.7), and 5.3 (IQR, 4.0-7.2), respectively. PSMA-VOL showed a moderate negative correlation with the SUVmean of the salivary glands (r = −0.44, P < 0.001), kidneys (r = −0.34, P < 0.001), and liver (r = −0.30, P < 0.001) and a weak negative correlation with the spleen SUVmean (r = −0.16, P = 0.002). Patients with a very high PSMA-VOL (quintile 5, ≥1,355 cm3) had a significantly lower PSMA uptake in the salivary glands, kidneys, liver, and spleen than did the control group, with an average difference of −38.1%, −40.0%, −43.2%, and −34.9%, respectively (P < 0.001). Conclusion: Tumor sequestration affects 68Ga-PSMA biodistribution in normal organs. Patients with a very high tumor load showed a significantly lower uptake of 68Ga-PSMA in normal organs, confirming a tumor sink effect. As similar effects might occur with PSMA-targeted radioligand therapy, these patients might benefit from increased therapeutic activity without exceeding the radiation dose limit for organs at risk.
Published online May 28, 2021
Im Titel ist "68" vor "Ga-PSMA-11" hochgestellt
Gesehen am 11.03.2022